Halal as a Contemporary Lifestyle: Encouraging Young People of Palu City to Develop with Halal Products - Ahmad Haekal; Ermawati, Ermawati; Fatimawali, Fatimawali; Basalamah, Rizqah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2023)
The push by Indonesia's younger generation to choose halal products is based on health awareness, the growth of the halal industry, and religious factors. While this drive is significant, there are still challenges that need to be overcome, such as lack of knowledge and constraints in halal manufacturing. In addition, purchasing halal products is often just a habit without awareness. Therefore, a strong religious commitment is needed to improve the understanding of halal products. The community service activity held by the Sharia Economics Study Program, Faculty of Economics and Islamic Business, Universitas Islam Negeri Datokarama Palu focused on increasing the understanding of halal products and halal lifestyles at SMA Negeri 1 Banawa by involving 50 participants. This activity consists of four stages: preparation, Focus Group Discussion, implementation, and evaluation. The evaluation results showed an increase in participants' understanding, although there were limitations such as limited coverage and non-comprehensive focus. Recommendations include expanding the scope of the program, adding sharia economic aspects, and evaluating the long-term impact on participants' religious commitment